Lead-Immobilization, transformation, and induced toxicity alleviation in sunflower using nanoscale Fe°/BC: Experimental insights with Mechanistic validations. Issue 1 (31st December 2022) - Aslam, Muhammad Rizwan; Waris, Muhammad; Muhammad, Ihsan; Ahmed, Maqbool; Khan, Zahid; Jabeen, Zobia; Yakoob Zehri, Mohammad; Arsalan, Muhammad; Rehman, Sidra; Alnasrawi, Abeer M.; Alkahtani, Jawaher; Elshikh, Mohamed S.; et al.
ABSTRACT: Lead (Pb) is a biologically non-essential element in the soil that brutally affects plants and other living organisms in soil; hence, its removal has become a worldwide concern. In this work, a multifunctional nanoscale zerovalent-iron assisted biochar (nFe°/BC) was used to minimize the Pb bioavailability in soil with aim of alleviating the Pb-induced toxicity in sunflower. Results revealed that nFe°/BC treatment had significantly improved plant growth (58%), chlorophyll contents (66%), intracellular permeability (60%), and ratio factor (93%), while decreasing the Pb uptake (78%) in plants. The Pb-immobilization and transformation mechanisms were proposed, suggesting that the presence of organic functional groups over the nFe°/BC surface might induce the complex formation with Pb by the ions exchange process in soil solution. The XPS analysis confirmed that surface-active components (Fe +, O 2−, O*, C═O) were the key factor for high Pb-immobilization within soil matrix. In addition, 87% of stable Pb species, including PbCO3, PbO, Pb (OH)2, and Pb-O-Fe were found in the soil surface. Current findings have exposed the diverse functions of nFe°/BC on plant health and established a phenomenon that nFe°/BC application could improve the plant agronomic attributes by regulating the homeostasis of antioxidants and Pb uptake.